2019
DOI: 10.1016/j.jenvman.2018.10.118
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sporicidal fumigation with methyl bromide or methyl iodide on electronic equipment

Abstract: The effect of sporicidal fumigation with methyl bromide or methyl iodide on the functionality of valuable electronic equipment was evaluated using desktop computers as surrogates under target conditions of 200-250 mg/L fumigant for 48 h at 24-30 °C and 75-85% RH. Methyl iodide fumigation damaged light-emitting diodes and optical films in computer displays that were powered-on during fumigation. After five months of post-fumigation operation, five out of six methyl-bromide-fumigated and all six methyl-iodide-fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In addition to this damage, MI fumigation resulted in further damage on LCD displays [33]. Based on these results, MB fumigation, rather than MI fumigation, was suggested to control fungal contamination on electronics [33]. Compared with the results of that study, our results demonstrated that EF is a suitable fumigant to control insect infestation on imported agricultural machinery, causing small amounts of damage to machine running.…”
Section: Measured Value Reference Valuementioning
confidence: 52%
See 4 more Smart Citations
“…In addition to this damage, MI fumigation resulted in further damage on LCD displays [33]. Based on these results, MB fumigation, rather than MI fumigation, was suggested to control fungal contamination on electronics [33]. Compared with the results of that study, our results demonstrated that EF is a suitable fumigant to control insect infestation on imported agricultural machinery, causing small amounts of damage to machine running.…”
Section: Measured Value Reference Valuementioning
confidence: 52%
“…These two fumigants did not coretal surface of the electronics, but they caused severe damage to rubber mateelectronics. In addition to this damage, MI fumigation resulted in further dam-D displays [33]. Based on these results, MB fumigation, rather than MI fumiga- 3 shows the measurement results of the electrical characteristics of the treated sample with a difference in the amount of fumigation from the sample before fumigation.…”
Section: Sorption Studies Of Ef and Reactivity Test On Alternator Ign...mentioning
confidence: 92%
See 3 more Smart Citations